2019
DOI: 10.1002/jocb.426
|View full text |Cite
|
Sign up to set email alerts
|

Creativity and Affective Temperament in Artistic and Non‐artistic Students: Different Temperaments are Related to Different Aspects of Creativity

Abstract: The relationship between creativity and temperament has been well documented in studies with professional artists. This also pertains to affective temperaments which constitute the vulnerability to affective disorders. However, less is known about the contribution of particular temperaments to specific components of creativity, for example, ideational fluency, or originality of thinking. The aim of the present study was to assess affective temperaments and creativity in artistic and non-artistic students. Nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
(88 reference statements)
1
3
0
Order By: Relevance
“…The Beta Standardized coefficient, .927 for the experimental group, and .794 for the control group of artistic works demonstration explain, respectively, 92.7% and 79.4% of the variance in the total score of artistic skills development predicted by artistic works demonstration. The result is in coherence with prior published research (Montgomery, 2017;Baldus & Wilson, 2016;Maureen, 2019;De La Cruz, 2017;Xhomara, 2019;Lekue, 2015;Ma, 2021;Yokochi & Okada, 2021;Lazutina et al, 2016;Ruotsalainen, 2017;De Backer et al, 2012;Zourntos, 2013;Necka & Hlawacz, 2013;Jaracz & Borkowska, 2020), who argued that artistic works demonstration predicts artistic skills development. As a final result, hypothesis # 2: Artistic works demonstration predicts artistic skills development of arts master students, is supported.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The Beta Standardized coefficient, .927 for the experimental group, and .794 for the control group of artistic works demonstration explain, respectively, 92.7% and 79.4% of the variance in the total score of artistic skills development predicted by artistic works demonstration. The result is in coherence with prior published research (Montgomery, 2017;Baldus & Wilson, 2016;Maureen, 2019;De La Cruz, 2017;Xhomara, 2019;Lekue, 2015;Ma, 2021;Yokochi & Okada, 2021;Lazutina et al, 2016;Ruotsalainen, 2017;De Backer et al, 2012;Zourntos, 2013;Necka & Hlawacz, 2013;Jaracz & Borkowska, 2020), who argued that artistic works demonstration predicts artistic skills development. As a final result, hypothesis # 2: Artistic works demonstration predicts artistic skills development of arts master students, is supported.…”
Section: Discussionsupporting
confidence: 89%
“…A lot of research is carried out to investigate the relationship between artistic works demonstration and different variables, including the artistic skills development of art students at university. Jaracz and Borkowska (2020), as well as Montgomery (2017), indicated that artistic works demonstration, such as dancing, painting or signing are connected significantly to artistic skills development; meanwhile, Xhomara (2019) found out that artistic collegial principalship impacts the artistic knowledge and competencies development. Other research study including different forms of artistic demonstration, such as dancing, signing, and sculpting works that are related significantly with development and improvement of artistic skills.…”
Section: Relationship Between Artistic Work Demonstration and Artisti...mentioning
confidence: 96%
See 1 more Smart Citation
“…This result can hardly be explained by the high overall level of cyclothymia in all groups enrolled, as the artists from the present study exhibited a lower level of cyclothymic temperament, compared to other studies. 32 , 33 The possible explanation for this result is that the group of artists in the present study consisted of chamber musicians and choir singers. In other studies, in which the affective temperament of the artists was assessed, representatives of other creative disciplines – writers, actors, and painters were also enrolled.…”
Section: Discussionmentioning
confidence: 77%